Factors Affecting Credit Risk in Nepalese Commercial Banks - Bhattarai, Seema (Economic Journal of Development Issues, 2023)
This study analyzes the factors affecting credit risk in Nepalese commercial banks. The study comprises data from 27 commercial banks from 2002 to 2020 A.D. For analysis, the Least Square Dummy Variable (LSDV) Regression for model I and Random Effect (RE) Regression Analysis for model II were performed. The effect of the independent variables on credit risk, using loan loss provision and non-performing loans, as proxies of it was examined. While comparing both models, the loan loss provisioning was found to better explain the credit risk. The growth rate of GDP, a macroeconomic variable, had a significant and positive effect on credit risk, which was unexpected whereas the control variable, the interbank interest rate, had a negative and significant effect on credit risk. Furthermore, the year dummy showed a relatively high requirement for loan loss provision, especially in the years 2019 and 2020, which may be due to COVID-19. The bank-specific variables like size, and government banks had significant and positive effects on credit risk. This implied that the merging of banks was not fruitful as it caused an increase in the total assets of banks, which would lead to an increase in the size of commercial banks. That increase in the size of commercial banks was found to increase credit risk. In addition, government-owned banks were found to have higher credit risk than other banks. The government should think about reforms through private sector participation in government-owned banks as another alternative to reduce credit risk.